Differential Signals-of-Opportunity Timing Back-Up Method on VHF Band for Critical Infrastructures - Martta-Kaisa Olkkonen; Maija Makela; Sanna Kaasalainen (IEEE Access)
This paper describes a back-up method for GNSS-free timing for power lines which is currently achieved using fibre links. The method is based on software-defined-radio technologies for monitoring low-frequency signals of opportunity (SoOp) serving as an alternative timing signal. Our solution utilizes FM broadcasts on VHF band to provide the SoOp and aims to distribute information to a large number of geographical locations. As time synchronisation capabilities are limited between two ends of a fibre link due to long distance, we propose utilizing the electrical length of a test probe at both ends as a baseline for the arrival time of the signal on multiple frequencies. After calibration, difference between the baselines accounts only for the error in the timing signal (SoOp). Making this value available online would serve a similar purpose as differential global navigation satellite system (DGNSS). We present results of a method validation in the laboratory. The slope of the baseline shows good agreement with a theoretical value. The values for the slope of the fitted regression lines are -3.06°/MHz and -5.04°/MHz for the theoretical and measured electrical length, respectively. We also demonstrate a method to improve the accuracy of estimating the environmental timing errors by introducing a mitigation method of the multipath effect at both ends. Then, the slope becomes -4.42°/MHz, which is closer to the expected, theoretical value. Thus, utilizing SoOp at both ends of fibre links, the error of open-air signals can be estimated with an increased accuracy.